EFFECTIVITY GIVING PROGRESSIVE MUSCLE RELAXATION TO DECREASE ANXIETY PREGNANCY WOMEN - Novea Putri Briliant; Rahajeng Siti Nur Rahmawati; Mika Mediawati (Indonesian Midwifery and Health Sciences Journal, 2022)
Background: Psychological changes are often experienced by pregnant women are anxiety, (28,7%) pregnant women in Indonesia experience anxiety. Several factors that cause anxiety in pregnant women are husband support, family support, age, environment conditions, parity and education. Anxiety can be reduce by relaxation. The effective relaxation for anxiety in pregnant woman is progressive muscle relaxation. This study aims to determain the effectiveness of progressive muscle relaxation to reduce anxiety in pregnant women. Method: This study uses the Study Systematic Mapping Method selected from the Google Scholar, Pubmed, and Garuda database. There are several points determined in the journal using the  year of publication, according to keywords, duplication, Full Text, and Indonesian or english, were selected using PICO so that 14 journals are obtained, which are then analyzed. Result: The highest level of anxiety in pregnant women was found third trimester, teenage pregnant women and primigravida. Anxiety levels can be reduced by giving progressive muscle relaxation. Progressive muscle relaxation intervention is not only effective in reducing anxiety but also prevents occurent of pregnancy complication. Coclusion: The highest level of anxiety occurs in teenage pregnant women with first pregnancy in third trimester. The most effective technique for reduce anxiety in pregnant women is progressive muscle relaxation intervention.